Sequentially rhodium-catalyzed enantioselective cycloisomerization-hydrogenation syntheses of alkylidene butyrolactone β-hydroxyethanes and alkylidene tetrahydrofuran β-aminoethanes - Muschelknautz, Nadine; Rominger, Frank; Müller, Thomas J. J. (Chemistry of heterocyclic compounds, 2018)
Open image in new windowThe enantioselective Rh-catalyzed Alder-ene cycloisomerization of ester- and ether-tethered alkyne allyl alcohols is an excellent entry to subsequent Rh-catalyzed one-pot hydrogenations in the sense of sequentially Rh-catalyzed processes to chiral alkylidene butyrolactone β-hydroxyethanes and alkylidene tetrahydrofuran β-aminoethanes, respectively, with excellent levels of enantioselectivity.
Gesehen am 14.06.2019